Reproductive phenology of climbers in a Southeastern Brazilian forest - Morellato, P. C.; LEitao, H. F. (Assn Trop Biol, 1996)
The reproductive phenology of the entire climber community (96 species of lianas and 40 species of vines) in a semideciduous forest in Southeastern Brazil (22 degrees 49'45''S; 47 degrees 06'33''W and 670 m altitude) was observed from March 1988 to February 1991. Phenological observations were made weekly by walking along a 10.5 km trail in the interior and at the forest edges of the Santa Genebra Reserve (SGR). The most species-rich families of climbers were Bignoniaceae (22), Malpighiaceae (17), Sapindaceae (12) and Asteraceae (12). Flowering patterns for woody lianas and herbaceous vines differed. Lianas had two flowering peaks: a minor peak in March in the transition from wet to dry season, and a major peak in October during the transition from dry to wet season. The flowering peak for herbaceous vines was in April. Fruiting of lianas was highly seasonal, with one peak in the late dry season (July-August). Fruiting for vines was less seasonal with a slight peak in March. These differences were consistent with the predominance of wind-dispersed fruits among lianas (72% of species) versus vines (52%). Low rainfall, high leaf fall, and strong winds during the dry season favor wind dispersal. More species of vines (40%) have animal-dispersed seeds than lianas (19%), and most vines fruited during the wet season. Phenological patterns of climbers and trees and treelets at SGR differed. The life form of lianas and their system of reserve economy may allow them to reproduce during periods unfavorable to trees. Displacement of peak flowering periods of trees and climbers pollinated by bees and small generalist insects may decrease competition for pollen vectors among species of these two groups of plants. Whereas the fruiting patterns of wind-dispersed trees and climbers at SGR were similar (most species fruiting during the dry season), animal-dispersed trees and treelets fruited throughout the year while animal-dispersed climbers exhibited a pronounced peak in late wet season. The distinct phenological patterns of climbers, generally complementary to those presented by trees, resulted in constant availability of Bowers and fruits throughout the year and enhances the importance of this plant group in Neotropical forests.
Keywords: Brazil; climbers; flowering; fruiting; lianas; phenology; seasonality; tropical forest; vines